Effect of interactive computer simulations on academic performance and learning motivation of Rwandan students in Atomic Physics - Gerard Tuyizere; Lakhan Lal Yadav (Institute of Advanced Engineering and Science, 2023)
Physics course is seen by both teachers and students as difficult when it comes to teaching and learning. Thus, there is a need to think of and integrate new and innovative ways of teaching which guarantee students an improved physics conceptual understanding. This study investigated the effect of interactive computer simulations on the academic performance and learning motivation of students. It used a quasi-experimental design with a quantitative approach. The participants were 163 senior five Rwandan students (80 students in a control group and 83 students in an experimental group). The investigation was done on students’ learning in atomic physics using physics education technology (PhET) simulations for the experimental group and conventional teaching methods for the control group. An atomic physics achievement test as a pre/post-test and a questionnaire related to motivation were designed and examined for reliability and validity. Data were analyzed by means of descriptive and inferential statistics. On both test scores and learning motivation, the results show that the experimental group performed better than the control group with noticeable statistically significant differences. This research recommended that the integration of interactive computer simulations can be helpful in teaching and learning physics in Rwanda and future research may focus on the effectiveness of these simulations in the teaching and learning of other science disciplines like Chemistry and Biology.